METODOLOGI PENELITIAN HUKUM SEBAGAI INSTRUMEN PENGEMBANGAN ILMU HUKUM DI INDONESIA - Godlif Nofiando Sitorus; Hery Chariansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Legal research methodology is not merely a technical sequence for collecting legal materials, but an epistemological instrument that determines the validity, direction, and social usefulness of legal science. This study examines the position, functions, and institutional requirements of legal research methodology in developing legal science in Indonesia. It uses normative legal research with statutory, conceptual, comparative methodological, and interdisciplinary approaches. Primary legal materials include the Constitution of the Republic of Indonesia of 1945, legislation on lawmaking, the national science and technology system, and judicial power. Secondary materials consist of books and verified journal articles published mainly from 2020 to 2026. The analysis applies legal interpretation, conceptual reconstruction, comparison, and synthesis. The findings show that methodology develops legal science through five connected functions: controlling legal validity, constructing concepts and doctrine, explaining the operation of law, evaluating justice and effectiveness, and translating knowledge into legal reform. An integrative model is proposed that combines a normative core, empirical verification, interdisciplinary explanation, digital traceability, ethical accountability, and policy translation. The development of Indonesian legal science therefore requires methodological congruence, transparent research procedures, stronger empirical literacy, reliable digital governance, and institutional standards that protect the prescriptive identity of legal science while remaining responsive to social change.